2014
DOI: 10.1037/fam0000020
|View full text |Cite
|
Sign up to set email alerts
|

Adoption status and family relationships during the transition to young adulthood.

Abstract: While adoptive family research has increased, most has focused on childhood and adolescence. Despite the known importance of parent-adolescent relationships drawn from the general population, we know little about how adoptive family relationships change or remain the same as adopted adolescents enter young adulthood. Utilizing the Sibling Interaction and Behavior Study, the purpose of this study is to build upon previous research to explore differences in conflict, closeness, and relationship quality between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…The small amount of research that has been done, however, suggests that positive aspects of parenting decline during the pre-teen and early teen years. This has been found for parental warmth (McGue et al, 2005; Rodríguez et al, 2014 8 ; Walkner and Rueter, 2014), parental closeness (Walkner and Rueter, 2014), parental support (Hafen and Laursen, 2009), as well as parental involvement, closeness and regard (McGue et al, 2005) – all of which decrease in pre-teen and teen years.…”
Section: Introductionmentioning
confidence: 82%
“…The small amount of research that has been done, however, suggests that positive aspects of parenting decline during the pre-teen and early teen years. This has been found for parental warmth (McGue et al, 2005; Rodríguez et al, 2014 8 ; Walkner and Rueter, 2014), parental closeness (Walkner and Rueter, 2014), parental support (Hafen and Laursen, 2009), as well as parental involvement, closeness and regard (McGue et al, 2005) – all of which decrease in pre-teen and teen years.…”
Section: Introductionmentioning
confidence: 82%
“…Importantly, sex differences in these results appeared to derive from the fact that mothers, not fathers, tended to be the custodial parent (Arnett, 2015; Wells & Johnson, 2001). Finally, this review underscored differences between adoptive and nonadoptive families, as levels of conflict (self‐reported and observed) were found to be higher in adoptive families than in nonadoptive families (Walkner & Rueter, 2014).…”
Section: Family Dynamics During Emerging Adulthood: What We Already Knowmentioning
confidence: 92%
“…Eight studies adopted both quantitative and qualitative methods: Five of these were categorized as mixed‐method studies and three as multimethod studies (Anguera, Blanco‐Villaseñor, Losada, Sánchez‐Algarra, & Onwuegbuzie, 2018). Of all the studies applying qualitative methods ( n = 21), 12 conducted interviews, six included open‐ended questions, one involved a focus group (Hamwey et al, 2019), one included both interviews and focus groups (Crocetti & Meeus, 2014), and one included family observation tasks (Walkner & Rueter, 2014).…”
Section: Methodological Features: How Do We Know What We Know?mentioning
confidence: 99%
“…Many Western studies have also explored the circumstances under which maternal mind-mindedness would vary. Previous studies have found that a mother's mind-mindedness is related to both parenting stress and negative behaviours towards the child during interaction at home (McMahon & Meins, 2012;Walker, Wheatcroft, & Camic, 2011).…”
Section: Introductionmentioning
confidence: 99%